Effect of Phase-Feeding Strategies on Growth Performance and Carcass Characteristics of Growing-Finishing Pigs: Strategies to Reduce Dietary Phases Using a Field Approach on Lysine Levels - M. B Menegat; S. S. Dritz; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2019)
The objective of this study was to evaluate whether simplification of phase-feeding strategies using a field approach with lysine specifications slightly below the estimated requirement for maximum growth rate is possible without compromising overall performance and carcass characteristics of grow-finish pigs. A total of 1,188 pigs (PIC; 359 × 1050; initially 63.5 lb body weight (BW)) were used in a randomized complete block design with 27 pigs per pen and 11 pens per treatment under commercial research conditions. Treatments consisted of four feeding programs with lysine specifications set at 98.5% of estimated requirements for maximum growth rate and 97.5% of maximum feed efficiency (F/G) for the weight range in each phase, except for the last phase of one of the 2-phase feeding programs which the lysine specifications were set for 100% of estimated requirements of maximum growth rate. Treatments were: a 2-phase feeding program with 0.91 and 0.72% standardized ileal digestible (SID) lysine (Lys) from 60 to 220 and 220 to 280 lb BW, respectively (2-phase Lys 98%); a 2-phase feeding program with 0.91 and 0.77% SID lysine from 60 to 220 and 220 to 280 lb BW, respectively (2-phase Lys 98%/100%); a 3-phase feeding program with 0.99, 0.79, and 0.72% SID lysine from 60 to 160, 160 to 220, and 220 to 280 lb BW, respectively (3-phase Lys 98%); and a 4-phase feeding program with 1.07, 0.91, 0.79, and 0.72% SID lysine from 60 to 110, 110 to 160, 160 to 220, and 220 to 280 lb, respectively (4-phase Lys 98%). The experimental diets were based on corn, distillers dried grains with solubles (DDGS), and soybean meal. Overall, from d 0 to 114, no evidence (P>0.05) for difference was observed in growth performance across feeding programs. There was no evidence for difference (P>0.05) for hot carcass weight and carcass yield, backfat thickness, loin depth, or percentage lean. Consequently, no evidence (P>0.05) for difference was observed in economics, with all phase-feeding programs resulting in similar income over feed cost (IOFC). In conclusion, simplification of phase-feeding strategies to fewer dietary phases in the grow-finish period with lysine set slightly below the requirements seems to be feasible. However, along with findings from our previous study, in feeding programs with fewer dietary phases and lysine set slightly below the requirements, growth performance can be compromised if initial BW and feed intake in the grow-finish period are lower than expected.
Keywords: lysine; phase-feeding pigs